Ukraine : Technical Assistance Report-State-Owned Enterprises-Fiscal Risk Management. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance Paper on Ukraine highlights that good progress has been made in improving the disclosure and management of fiscal risks since the embedding of fiscal risks in the Budget Code in December 2018. The mission refined the financial model to analyze risks relating to Naftogaz that had been developed on the October 2018 mission. Despite updating the assumptions, the modelling still shows that the anticipated loss of transit gas revenue will have a significant negative impact on the Ukraine budget from January 2020. Appropriate mitigating action could ameliorate this negative impact, but there will still be a significant reduction in the inflows to the budget from Naftogaz. The next steps recommended by the mission include that Naftogaz, Ukrainian Railways and Energoatom models should be discussed with the State-owned Enterprises (SOE) and refined and that coverage should be expanded to include other major SOEs.